How is Financial Literacy at PT. Moya Indonesia - Daud, Maiercherinra; Nurlia; Lintang, Jane; Baptista Halik, Johannes (Journal of Management, 2023)
This study intends to ascertain the impact of financial literacy on managing risk of loss at PT. Moya Indonesia, specifically with regard to financial knowledge, financial attitude, and financial behavior management. It also seeks to ascertain the impact of risk management comprehension on managing risk of loss at PT. Moya Indonesia. to ascertain how the degree of financial literacy at PT. Moya Indonesia affects the degree of understanding of risk management in terms of financial knowledge, financial attitudes, and financial management behavior. Additionally, to ascertain how financial literacy levels affect management financial behavior, financial attitudes, and financial knowledge